A comparative study of strategies for containing the COVID-19 pandemic in Gulf Cooperation Council countries and the European Union. (2021) - Alanezi, Fahad; Althumairi, Arwa; Aljaffary, Afnan; Alfayez, Asma; Alsalman, Demah; Alhodaib, Hala; AlShammari, Maha M.; Aldossary, Reem; AlThani, Bashair; Alghamedy, Fatemah; Alanzi, Turki M.
Abstract: Background: The COVID-19 pandemic has impacted every aspect of human lives including health, businesses, and lifestyles. In spite of governments implementing various strategies across the globe, the pandemic is still expanding with increasing numbers of positive cases. In addition, countries are reopening and easing lockdown restrictions in order to get their economies back on track, and this has led to an increase in the transmission of novel coronavirus. Therefore, it is essential to regularly review the containment strategies employed in different regions in order to understand the characteristics of COVID-19 transmission and to formulate a future course of actions. Objective: The objective of this study is to review the COVID-19 transmission statistics in Gulf Cooperation Council (GCC) and European Union (EU) countries, and to compare these data with the various containment strategies implemented for containing the spread of the virus. Methods: A review method was adopted along with different statistical methods for comparing and analyzing COVID-19 data and containment strategies. Transmission types and the Case Fatality Rate (CFR) in the countries in both regions are used to present the current state of the pandemic. In addition, changes in the number of COVID-19 cases are compared with the mitigation and suppression strategies implemented in both regions and their impact is analyzed. Results: Countries in the EU were slow in reacting to the pandemic, as delays are observed in the implementation of mitigation strategies. However, suppression strategies were implemented soon after mitigation strategies. GCC countries, on the other hand, were quick to react, and they implemented both mitigation and suppression strategies simultaneously, as soon as the pandemic emerged. The CFR was found to be low among GCC countries compared to EU countries. In addition, a second wave of transmission was observed in the EU, whereas in GCC countries there has been no second wave, although a gradual increase in the number of cases is observed. Community transmission was observed among the majority of countries in both GCC and EU countries. Conclusions: With the reopening of markets, the focus of governments should be on developing integrated user-centric preventive strategies, with a blend of awareness creation, motivation, and support.